A REPORT ON COMPARATIVE MORPHOLOGY OF EGG MASSES AND EGGS IN PULMONATE GASTROPODS INDOPLANORBIS EXUSTUS (DESHAYES 1834) AND LYMNAEA ACUMINATA LAMARCK 1822 - G. S. PANDE; S. P. CHAUHAN; R. D. TAK (The Bioscan, 2020)
The present investigation deals with the comparative study of egg mass and egg morphology in freshwater snails I. exustus and L. acuminata. These snails lay eggs embedded in gelatinous strip called egg mass. The comparative morphometric measurements of egg masses and eggs showed significant variations with respect to morphology between two snails. The egg masses of I. exustus measured about 16.83 mm×3.13 mm and were significantly smaller (P >0.05) than those of L. acuminata which measured about 18.28mm × 3.92 mm. The eggs of L. acuminata measured 1025.05μm × 723.44μm and were significantly smaller (P >0.05) than those of I. exustus which measured about 1149.17μm × 888.35μm. The number of eggs/egg mass was also found to vary significantly (P >0.05) between two snails studied. The snail L. acuminata had more eggs/egg mass with a mean number of eggs/egg mass 41.45 ± 22.10 as opposed to 22.05-± 4.88 in I. exustus. From the analysis of the results obtained, it can be concluded that there are significant differences between morphological parameters of eggs and egg masses of freshwater snails L. acuminata and I. exustus.